Studies into the technical feasibility of the Transverse Horizontal Axis Water Turbine - McAdam, R (2011)
The Transverse Horizontal Axis Water Turbine (THAWT) has been proposed as a tidal device which can be easily scaled and requires fewer foundations, bearings seals and generators than a more conventional axial-flow device. The THAWT device is a horizontally deployed variant of the Darrieus cross-flow turbine, in which the blades can be oriented into a truss configuration to produce long, stiff multi-bay rotors. This thesis establishes and combines a set of numerical models, which predict the hydrodynamic and structural performance of the THAWT device, with sufficient confidence to assess the feasibility of such a device at a full scale installation and to optimise its performance. Tests of 1/20th scale experimental models of the THAWT device have demonstrated that the truss configured device is capable of producing power with an efficiency close to that of the parallel configured turbine. In addition, variations in the configuration of the scale models have indicated how several design parameters affect the hydrodynamic performance of the device. A two-dimensional Navier-Stokes blade element model has been developed, in which the THAWT device is represented using an actuator cylinder. The addition of a hydrostatic free surface deformation correction has resulted in a model which is capable of matching experimental results with sufficient fidelity and accuracy. Blade loads from the numerical hydrodynamic model have been applied to a beam finite element analysis, to predict the stresses induced in the hydrofoils of the THAWT device. The numerical and hydrodynamic models are combined with a Linear Channel Momentum model to predict the performance of the THAWT device at a full scale tidal location. The effect that the device has on the channel flow indicates how much energy is available for extraction and how this energy might be most efficiently obtained. When considering material fatigue the analysis suggests that the structural design considerations dominate over the hydrodynamic considerations.